Analysis on Reports of Statistical Testing for Mean Differences in Articles in the Korean Journal of Women Health Nursing. - Jun Eun-Mi; Lee Eun-Hee; Kim Jeung-Im; Kang Hee Sun; Oh Hyun Ei; Lee, Eun-Joo; Cheon, Suk-Hee (Korean Journal of Women Health Nursing, 2011)
Purpose: This study was done to evaluate the accuracy and adequacy of research studies reporting statistical testing for mean differences in studies of the Korean Journal of Women Health. Methods: Among articles published in the journal from 2007 to 2009, 75 studies using t-test, χ2-test, and ANOVA were identified. The studies were evaluated using structured analysis format for adequacy of research title, accuracy of statistical methods and presentation styles, and errors in reported statistical outcomes. Results: In this study, the research titles generally reflected the purpose of research and study designs. Thus the research titles were quite comprehensive. Also, there was compatibility between the research purpose and research design. Most important though, many errors were identified in the tables of results of the statistical analysis in articles published from 2004 to 2006. Conclusion: Over six years, 2004 to 2009, accuracy and adequacy of research studies has improved in many aspects. In order to enhance the completeness of the published papers and to be an internationally recognized nursing journal, close attention of the researchers, reviewers and editors is necessary to avoid errors and present adequate and accurate research.